Pembelajaran Afeksi - Misbahul Munir (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2017)
In school learning; In addition aspects of intellectual formation to shape the intelligence of learners and the formation of skills to develop competence, so the learners must have motoric skills, then the attitudes of learners is an aspect that is not less important. The process of education is not only forming intelligence or providing certain skills, but also establish and develop attitudes so that children have an accordance with the norms prevailing in society. Affective learning is related to value, which is difficult to measure because it involves awareness of someone who grows from within. This is not easy in the planting so it takes a serious and continuous effort both in school and when under the supervision of parents at home. Because of the importance of affective learning it is a necessity for educators to be more intensive in its implementation and do not consider if the affective learning does not include interests in making students as a superior generation who will live in the future and ready in all of challenges